Ushul Fiqih Menurut Paradigma Filsafat Ilmu (Kajian Ontologi, Epistemologi, dan Aksiologi) - Dedi, Syarial (AL-ISTINBATH : Jurnal Hukum Islam, 2020)
This paper aims to examine how the ontology, epistemology and axiology (paradigm of philosophy of science) ushul fiqih. This is very important because ushul fiqih has its own epistemological construct that cannot be separated from the principles of science in an Islamic perspective which are clearly at odds with the West. This misunderstanding raises negative accusations against the science of ushul fiqih. Even though usul fiqih is the highest degree of science, because it combines naql and 'aql. This is a library research using content analysis method. This study concludes that the three pillars (ontology, epistemology and axiology) are closely related. The combination of the power of revelation and reason is the hallmark of ushul fiqih epistemology. Revelation is positioned at the highest level, because it comes from the omniscient. Intellect is positioned at a lower level hierarchically, implying that reason submits to the truth of revelation. In this construct, it is revelation that becomes the standard of truth.